HUSK-SAND CHARCOAL IMPROVES THE CHEMICAL QUALITY OF INCEPTISOL SOIL FOR LETTUCE MICROGREEN - Suryani Suryani; Yunita Sabri; Yustitia Akbar; Rahmawati Rahmawati; Desriana Desriana; B.A Martinus; Raimon Raimon (JURNAL KATALISATOR, 2022)
Inceptisol soil is a soil that is not good chemical and physical quality for the cultivation of lettuce microgreen. However, microgreen is a plant that has many benefits. Microgreens can fight free radicals, are useful as antioxidants, relieve the workload of damaged kidneys and lower bad cholesterol levels, and can reduce the risk of Alzheimer's disease. Several studies have been conducted to improve the soil quality of inceptisol. But improving its chemical quality by using a mixture of husk charcoal and sand and proving the change through the cultivation of lettuce microgreen has not been done much. The purpose of this study is to study the improvement of the chemical quality and physics of inceptisol soil using a mixture of husk charcoal and sand by cultivating lettuce microgreen in the land. This research is a mixture of field research and analysis in the laboratory. before planting and 2 weeks after planting, the land is measured pH, P determination is available by bra method, N conjecturing by means of distillation and spectrophotometry. Determination K uses HCl extraction method. Determination of Zn, Fe, and Ca using DTPA extraction. For analysis of cultivation, results is with RAK, where there are 4 groups with 5 Deuteronomy. The result was a change in pH from 4.7 to 6.9. The content of P, N and K changes from ineligible to fulfilling the requirements for lettuce plants. The results of the analysis provide real different information.